At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Let f(x) = - 3x – 1 and g(x) = x^2 – 3.
Find (fog)(-1).
Then (fog)( - 1)= (Simplify your answer.)


Sagot :

Answer:

(fog)(-1)=5

Step-by-step explanation:

Let f(x) = - 3x – 1 and g(x) = x^2 – 3.

(fog)=-3(x^2-3)-1

(fog)=-3x^2+9-1

(fog)=-3x^2+8

(fog)(-1)=-3(-1)^2+8

(fog)(-1)=-3+8

(fog)(-1)=5